Etiology of Inguino-Scrotal/Labial Swelling in Children and Its Pattern of Management: A Cross-Sectional Study (Jalalabad Medical Journal, 2026)
Inguino-scrotal and inguino-labial swellings occur due to inguinal hernia, hydrocele, testicular torsion, epididymo-orchitis, undescended testis, inguinal lymphadenitis, inguinal abscess, testicular tumour and rarely hydrocele of the canal of Nuck. This cross-sectional study was conducted in the department of paediatric surgery, Jalalabad Ragib-Rabeya Medical College Hospital, during the period of two and a half years from January 2021 to July 2023 to find out the causes of inguino-scrotal/labial swelling in children and its pattern of management. A total of 125 patients of inguino-scrotal/labial swellings, aged up to 14 years were included. Children with hydrocele whose age was below two years were excluded from this study. Patients were diagnosed by history, examination and investigation. Patients were managed surgically and conservatively. Incidence of inguino-scrotal/labial swelling was 2.5%. The age of the patients ranged from 29 days to 14 years, with the mean age of 5.17 (SD 2.85) years. Majorities (61.6%) of the patients were below the age of 5 years. The male-female ratio was 10.36:1. More than half (56.8%) of the swellings were on the right side. Inguinal hernia (44.8%) was the commonest cause of inguino-scrotal/labial swelling, followed by hydrocele (25.6%). About 91.2% of patients were treated surgically and 8.8% of patients received medical treatment. The outcome was uneventful/cured in 94.4% of cases, while 5.6% of patients developed some form of complications. Postoperative hospital stay ranged from 2 to 8 days with a mean of 2.76 (SD 1.14) days. So, it may be concluded that inguinal hernia is the commonest cause of inguino-scrotal/labial swelling in children. The outcome of inguino-scrotal/labial swelling is excellent.Jalalabad Med J 2025; 22 (2): 78-83